PENGARUH MOTIVASI BELAJAR DAN LINGKUNGAN TEMAN SEBAYA TERHADAP MINAT MELANJUTKAN STUDI KE PERGURUAN TINGGI DI SMK SUKAWATI GEMOLONG - Rio Dian Permana (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2019)
This study aims to determine whether or not: (1) learning motivation toward the interest in continuing study to college, (2) the influence of the peer group toward the interest in continuing study to college, and (3) the influence of learning motivation and peer group toward the interest in continuing study to college. This study is a quantitative correlational study. The population in this study is students of class XII at SMK Sukawati Gemolong. Samples were taken using a proportional random sampling technique. There is a sample of 92 respondents consisting of 12 men and 80 women. This study uses observation, documentation, and questionnaires for data collection methods. Data were analyzed by using multiple linear regression analysis with SPSS 23 program. Based on the analysis, it is found: (1) there is a significant influence of learning motivation toward the interest in continuing study to college at SMK Sukawati Gemolong ( or ), (2) there is a significant influence of peer group toward the interest in continuing study to college at SMK Sukawati Gemolong ( or ), and (3) there is a significant influence of learning motivation and peer group together toward the interest in continuing study to college ( or ). Regression equation Y = 1,486 + 0,473 X1 + 0,373 X2. The relative contribution of learning motivation is 66%. The relative contribution of the peer group is 34%. The effective contribution of learning motivation is 35,30%. The effective contribution of the peer group is 18%.